Standardization of Gleason grading among 337 European pathologists. Issue 2 (13th December 2012) - Egevad, Lars; Ahmad, Amar S; Algaba, Ferran; Berney, Daniel M; Boccon‐Gibod, Liliane; Compérat, Eva; Evans, Andrew J; Griffiths, David; Grobholz, Rainer; Kristiansen, Glen; Langner, Cord; Lopez‐Beltran, Antonio; et al.
<x xml:space="preserve">Abstract</x> Aims: The 2005 International Society of Urological Pathology (ISUP) modification of Gleason grading recommended that the highest grade should always be included in the Gleason score (GS) in prostate biopsies. We analysed the impact of this recommendation on reporting of GS 6 versus 7. Methods and results: Fifteen expert uropathologists reached two‐thirds consensus on 15 prostate biopsies with GS 6–7 cancer. Eighty‐five microphotographs were graded by 337 of 617 members of the European Network of Uropathology (ENUP), representing 19 countries. There was agreement between expert and majority member GS in 12 of 15 cases, while members upgraded in three cases. Among members and the expert consensus, a GS >6 was assigned by 64.5% and 60%, respectively. Mean member GS was higher than consensus GS in nine of 15 cases. A Gleason pattern (GP) 5 was reported by 0.3–5.6% in 10 cases. Agreement between consensus and member GS was 58.2–89.3% (mean 71.4%) in GS 6 cases and 46.3–63.8% (mean 56.4%) in GS 7 cases (P = 0.009). Conclusions: While undergrading of prostate cancer used to be prevalent, some now tend to overgrade. Minimum diagnostic criteria for GP 4 and 5 in biopsies need to be better defined. Image libraries reviewed by experts may be useful for standardization.